Rhinogobius houheensis, a new species of freshwater goby (Teleostei: Gobiidae) from the Houhe National Nature Reserve, Hubei province, China - Wanghe, Kunyuan; Hu, Faxiang; Chen, Minhao; Luan, Xiaofeng (Zootaxa, 2020)
A new freshwater goby, Rhinogobius houheensis, is described based on 40 specimens in a freshwater stream from the Houhe National Nature Reserve, Hubei Province, China. The new species can be distinguished from all its congeneric species by the following combination of characters: thee first dorsal fin rays VI, the second dorsal fin rays I/9-I/10; anal fin rays I/7-I/8; pectoral-fin rays 16–17; longitudinal scale series 37–40; transverse scales 12–14; predorsal scale series 0; and vertebrae counts 12+18=30. The first three spinous rays in the first dorsal fin are colored with two dark-blue stripes and one black spot in alive.